Environmental Education activity with children - Aline Vasconcelos Marques; Andréa Terezinha Pereira; Anita E. dos Santos; Laurete S. Lichtenfelz (Universidade Federal de Santa Catarina, 2000)
The Environmental Education Project is one of the goals of the project management teacher Fatima Ferreira, submitted before the school community on 24/06/98. This project's technical coordinator Salete Santos, PhD in Production Engineering, under the guidance of Professor Dr. Rick and the teaching staff is composed of educators working in the Nei St. Anthony of Padua.